UPAYA PENINGKATAN KEMAMPUAN GURU DALAM MEMBUAT MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DI SMKN 1 BATIPUH - M. Nasir; Dwi Sudarno Putra; Dedi Setiawan; Wagino Wagino (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
The rapid influence of the rapid development of information and communication technology (ICT) requires educators to harness the technological results in the learning process and gain access to broader (global) knowledge. Likewise educators are required to develop skills to make learning media so that learning can run effectively, interesting, generate motivation and provoke creativity of learners. This activity aims at (a) Developing teacher competence in designing instructional media based on information and communication technology (b) Developing teachers' skill in making learning media and (c) Increasing teacher's insight in utilizing technology and communication. Through the community service activities of the State University of Padang held training efforts to improve the ability of teachers in making meida learning based on information technology in SMKN 1 Batipuh. The method of devotion chosen is the training with the target of 25 teachers with the material of designing, manufacturing and using learning media with power point, lecture training method, question and answer, demonstration and workshop. Presentation of theory and practice held for 2 days located at SMKN 1 Batipuh West Sumatra. The result of the dedication activity is 25 participants have competence marked by the improvement indicator on the ability of designing, making and using learning media with power point.